Pengaruh Suku Bunga, Nilai Tukar, dan Infrastruktur Terhadap Foreign Direct Investment di Indonesia - Lilis Apriliani Lilis; Hilmiatus Sahla (Ali Institute of Research and Publication, 2026)
This study aims to analyze the influence of interest rates, exchange rates, and infrastructure on foreign direct investment (FDI) in Indonesia. The data studied in this study are secondary data. This study uses a quantitative research method based on associative approach in the form of time series data for the period 1995-2024 collected from the World Bank and BPS. The population and sample are 30 abservational data. The data analysis technique used the classical assumption test which includes normality, multicollinearity, heteroscedasticity, and autocorrelation tests. Subsequently, multiple linear regression analysis, the hypothesis test and the coefficient of determination test with the Eviews 13 statistical tool. The results of the study indicate that partially the interest rate variable does not have a significant effect on foreign direct investment with a probability score of 0.05589 > 0.05. The exchange rate variable has a significant effect on foreign direct investment with a probability score of 0.0354 < 0.05. The infrastructure variable also has a significant effect on FDI with a probability score of 0.0000 < 0.05. Simultaneously, interest rates, exchange rates, and infrastructure significantly influence FDI with a calculated f value of 67.52277 > Ftable 2.991 and a probability score of 0.000000 < 0.05. The Adjusted R Square score of 0.8731 shows that variations in foreign direct investment can be explained by the variables of interest rates, exchange rates, and infrastructure, namely 87.31%, and the other 12.69% is explained by other aspects outside the study. Keywords: Interest Rates, Exchange Rates, Infrastructure, Foreign Direct Investment